Análise numérica de vigas mistas protendidas com interação parcial - Lima, Ésio Magalhães Feitosa (2018)
The protension technique, however traditionally referenced to concrete structures, has been shown to be very beneficial and useful when used in composite structures. Recent works indicate that when pretensioning composite beams through the insertion of steel cables, several benefits can be obtained: elastic behavior in situations of high load, greater capacity resistant and reduction of useful height of the beam. In composite beams the interaction that occurs at the interface of the steel and the concrete slab has influence on the structural behavior of the part. In practice, for a composite element to have no relative slip between the materials, the stiffness at the contact interface should be quite high, which leads to the use of a large number of shear connectors. Based on the need to obtain more information about this technique, the present work aims to realize a numerical analysis of composite beams with external protension in a nonlinear analysis, considering the possibility of sliding at the contact interface of the composite beam. The code used for the numerical analysis was developed through the Matlab program, and was based on the Finite Element Method. This tool consists of finite elements of frame and finite elements of protension cable, both based on Euler-Bernoulli beam theory. In relation to the geometric non-linearity, the Green-Lagrange deformations were considered as the result of the total Lagrangian formulation. For the representation of the material nonlinearity, constitutive models were considered present in norms and relevant papers. For the integration of the internal forces and the tangent matrix in the cross section and along the longitudinal axis, the Slice Method, the Gauss Quadrature Method and the Lobatto Quadrature were used. Finally, the results obtained by the program were compared with experimental, analytical and numerical results of specific examples available in the technical literature, and it was verified that the developed code satisfactorily represents the material and geometrical non-linear behavior of the prestressed composite beams which is considered partial interaction.